2007
DOI: 10.1152/jn.01095.2006
|View full text |Cite
|
Sign up to set email alerts
|

Motor Adaptation as a Greedy Optimization of Error and Effort

Abstract: Motor adaptation to a novel dynamic environment is primarily thought of as a process in which the nervous system learns to anticipate the environmental forces to eliminate kinematic error. Here we show that motor adaptation can more generally be modeled as a process in which the motor system greedily minimizes a cost function that is the weighted sum of kinematic error and effort. The learning dynamics predicted by this minimization process are a linear, auto-regressive equation with only one state, which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
182
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(201 citation statements)
references
References 42 publications
16
182
2
1
Order By: Relevance
“…Motor learning uses sensory feedback to modify feedforward commands and improve performance (Johansson and Cole, 1994). Existing learning schemes from neuroscience or robotics based on iterative learning or adaptive control change the feedforward command based on a monotonic function of the kinematic error in joint or muscle space (Kawato et al, 1987;Slotine and Li, 1991;Katayama and Kawato, 1993;Gribble and Ostry, 2000;Thoroughman and Shadmehr, 2000;Donchin et al, 2003;Emken et al, 2007) (see Fig. 1 A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor learning uses sensory feedback to modify feedforward commands and improve performance (Johansson and Cole, 1994). Existing learning schemes from neuroscience or robotics based on iterative learning or adaptive control change the feedforward command based on a monotonic function of the kinematic error in joint or muscle space (Kawato et al, 1987;Slotine and Li, 1991;Katayama and Kawato, 1993;Gribble and Ostry, 2000;Thoroughman and Shadmehr, 2000;Donchin et al, 2003;Emken et al, 2007) (see Fig. 1 A).…”
Section: Methodsmentioning
confidence: 99%
“…Our novel algorithm learns the time-varying motor commands to individual muscles that produce the same force and mechanical impedance observed when humans adapt to changes in environmental forces, including those arising from instability in the environment. It departs significantly from algorithms based on optimization (Burdet and Milner, 1998;Harris and Wolpert, 1998;Stroeve, 1999;Todorov, 2000;Todorov and Jordan, 2002;Guigon et al, 2007;Trainin et al, 2007;Izawa et al, 2008) as it predicts the transients of learning, as well as from existing supervised learning schemes (Kawato et al, 1987;Slotine and Li, 1991;Katayama and Kawato, 1993;Gribble and Ostry, 2000;Thoroughman and Shadmehr, 2000;Donchin et al, 2003;Emken et al, 2007) because they have no mechanism to counteract mechanical instability.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with studies that found that minimization of control effort plays a role in kinetic adaptation to novel dynamic environments, but is less effective than minimization of execution errors [182,51].…”
Section: Control Effortsupporting
confidence: 92%
“…Still, the disadaptation occurred at a much slower rate than when kinematical errors were allowed to occur. Further evidence for a contribution of muscular effort in adaptation was recently provided by Emken and colleagues [51]. They examined the adaptation to an externally applied force field during the swing phase of walking and showed that a model describing the temporal evolution of error [208,183] could be derived from minimization of a cost function that is a weighted sum of the execution error and control effort.…”
mentioning
confidence: 97%
See 1 more Smart Citation